Derivation of verbs attested in the old Lithuanian scripts: infixed and sta-stem anticausatives - Pakalniškienė, Dalia (Lietuvių kalba, 2020)
The article presents the analysis of infixed and sta-stem verbs opposed to ia-stem verbs attested in the old Lithuanian scripts, investigating the opposition causative/anticausative. The research has shown that this morphosemantic opposition was amply testified in the earliest Lithuanian written sources – 59 correlations of this type were recorded in total. More than 50 percent of the equivalents of the oppositions attested exist in the Latvian language as well. This suggests that the causative/anticausative formation belongs to the Eastern Baltic period, and has been crucial to the productivity of the class of infixed and sta-stem verbs. Although not so abundant, the correspondences of the oppositions found in the Slavic and Germanic languages presuppose an even earlier chronology of decausation. The regularity of the semantics and formal structure of the oppositions allow the relations of the opposites to be treated as derivative. This is particularly true in the case of the abundant reflexes of “complex-root” oppositions such as CeRC/CiRC. The abundance of non-present and prefixed forms of the analysed verbs testifies to the specificity of this flexional class in terms of actionality: inchoative, completive, limitative or punctual meaning realised by corresponding prefixes was important for the development of the morphosemantic uniformity of decausatives and has inspired new patterns of word formation, the durative/terminative opposition and the derivation of the denominatives in particular. The study of the causative/anticausative verbal opposition in the old Lithuanian scripts is significant for the history of Lithuanian infixed and sta-stem verbs and for a typological linguistic research.
Keywords: infixed and sta-stem verbs; causatives; anticausatives; decausatives; apophony